Diaquabis[N-(2-fluorobenzyl)-N-nitrosohydroxylaminato-κ2O,O′]nickel(II) - Olga Kovalchukova; Ali Sheikh Bostanabad; Adam Stash; Svetlana Strashnova; Igor Zyuzin (Acta Crystallographica Section E, 2014)
In the centrosymmetric title compound, [Ni(C7H6FN2O2)2(H2O)2], the NiII cation is in a slightly distorted octahedral environment and is surrounded by four O atoms from the N—O groups of the organic ligands [Ni—O = 2.0179 (13) and 2.0283 (12) Å], and two water molecules [Ni—O = 2.0967 (14) Å]. The N-(2-fluorobenzyl)-N-nitrosohydroxylaminate monoanions act as bidentate chelating ligands. In the crystal, the Ni cations in the columns are shifted in such a way that the coordinated water molecules are involved in the formation of hydrogen bonds with the O atoms of the organic species of neighbouring molecules. Thus, a two-dimensional network parallel to (100) is built up by hydrogen-bonded molecules.